2004
DOI: 10.1016/s0006-3495(04)74124-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Probes: What Is the Range of Their Interaction with the Environment?

Abstract: We performed pressure-tuning hole-burning experiments on a modified cytochrome c protein in a glycerol/buffer glass. The shift and the broadening of the holes were investigated for various frequencies within the inhomogeneous band. On the basis of a simple model, we were able to estimate the interaction range between chromophore and protein. It is approximately 4.5 A. The parameters that enter the model are the compressibility, the static mean-square displacement, the inhomogeneous width, and the average spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 29 publications
3
39
0
Order By: Relevance
“…Two lecturers discussed the effect of pressure on the thermodynamics of folding. Joseph Friedrich from the Technical University in Munich (Germany) elaborated on the fascinating elliptic form of the phase diagram of proteins in the temperature-pressure plane and showed how solvent interactions change with pressure, as reflected in the spectra of the chromophore of Zn-cytochrome c. [12] Roland Winter (Dortmund, Germany) showed that temperaturepressure studies, combined with a variety of spectroscopic methods, can be used to parameterize an empirical energy landscape for a folding protein. [13] He also discussed a sophisticated pressure-jump spectrometer and its application to folding.…”
Section: Time-resolved Infrared Spectroscopymentioning
confidence: 99%
“…Two lecturers discussed the effect of pressure on the thermodynamics of folding. Joseph Friedrich from the Technical University in Munich (Germany) elaborated on the fascinating elliptic form of the phase diagram of proteins in the temperature-pressure plane and showed how solvent interactions change with pressure, as reflected in the spectra of the chromophore of Zn-cytochrome c. [12] Roland Winter (Dortmund, Germany) showed that temperaturepressure studies, combined with a variety of spectroscopic methods, can be used to parameterize an empirical energy landscape for a folding protein. [13] He also discussed a sophisticated pressure-jump spectrometer and its application to folding.…”
Section: Time-resolved Infrared Spectroscopymentioning
confidence: 99%
“…It has been observed in experiments that denaturation of the native structure (pressure denaturation) [2][3][4][5][6] and dissolution of amyloid-fibrils [7][8][9] and virus assemblies [10] occur at high pressures. A common feature of these phenomena is that the volume change upon the pressure denaturation and dissociation is negative [3,6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of the pressure-denatured structure of a protein have been analyzed in detail [2,[4][5][6][12][13][14][15][16]. For example, the pressure dependence of the radius of gyration, R g , of staphylococcal nuclease has been studied using synchrotron X-ray small-angle scattering [2] and small-angle neutron scattering [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Lesch et al (Lesch, Schlichter et al 2004) the integrity of protein complexes can be monitored with sub-nanometer spatial resolution by the so-called molecular probe method. Fig.…”
mentioning
confidence: 99%